TLQP-21 changes in response to a glucose load. (February 2021) - Corda, Giulia; Noli, Barbara; Manconi, Barbara; Brancia, Carla; Pellegrini, Manuela; Naro, Fabio; Olianas, Alessandra; Ferri, Gian-Luca; Cocco, Cristina
Highlights: TLQP-21 is hypoglycemic. Upon hyperglycaemia pancreatic TLQP-21 decreases while plasmatic TLQP-21 increases. TLQP-21 acts as hormone. Abstract: Background: The TLQP-21 peptide potentiates glucose-stimulated insulin secretion, hence we investigated its endogenous response to glucose. Methods: Fasted mice received intraperitoneal glucose (3 g/kg), or saline (controls), and were sacrificed 30 and 120 min later (4 groups, n = 6/group). We investigated TLQP-21 in pancreas and plasma using immunohistochemistry, enzyme-linked immunosorbent assay (ELISA) and high performance liquid chromatography (HPLC), as well as TLQP-21 receptors (gC1q-R and C3a-R1) expression in pancreas by immunohistochemistry. Results: In pancreas, TLQP-immunoreactivity (TLQP-ir.) was shown in insulin-, glucagon- and somatostatin-containing cells. Upon glucose, TLQP-ir. decreased at 30 min (∼40 % vs. controls), while returning to basal values at 120 min. In all groups, C3a-R1 was localized in ∼50 % of TLQP labelled islet cells (mostly central), while gC1q-R was detected in ∼25 % of TLQP cells (mainly peripheral). HPLC fractions of control pancreas extracts, assessed by ELISA, confirmed the presence of a TLQP-21 compatible-form (∼2.5 kDa MW). In plasma, TLQP-ir. increased at 30 min (∼30 %), with highest concentrations at 120 min (both: p< 0.05 vs. controls), while HPLC fractions showed an increase in the TLQP-21 compatible form. Conclusions: Upon hyperglycaemia, TLQP-21 would be released from islets, to enhance insulin secretion but we cannot exclude an autocrine activity which may regulate insulin storage/secretion.